Analysis Of The Effect Of Excess Air On Boiler Combustion Efficiency At PT PLN Nusantara Power Paiton Unit 9 - Mochammad Brillian Bima Wicaksono; Royb Fatkhur Rizal (International Journal of Health Engineering and Technology, 2026)
Boiler combustion efficiency is one of the important factors affecting the performance and operational reliability of steam power plants. One of the parameters that significantly influences combustion efficiency is excess air, which refers to the amount of air supplied exceeding the theoretical combustion requirement. This study aims to analyze the effect of excess air on boiler combustion efficiency at PT PLN Nusantara Power Paiton Unit 9. The research method used is a descriptive quantitative approach through field observations and operational data analysis obtained from the Distributed Control System (DCS). The analyzed parameters include oxygen content (O₂), excess air, boiler load, flue gas temperature, air flow, fuel flow, heat loss, and combustion efficiency. The results show that increasing excess air causes higher heat loss due to the increasing amount of heat carried away by flue gas, resulting in decreased boiler combustion efficiency. At low boiler loads, excess air tends to increase because the combustion process becomes less stable and requires additional air to maintain flame stability. Meanwhile, optimal excess air conditions provide more stable combustion, lower heat loss, and higher combustion efficiency. Therefore, controlling excess air properly is essential to maintain optimal boiler performance, improve operational efficiency, and reduce energy losses in the power generation system.